2012
DOI: 10.1080/14786419.2010.534994
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of composition and biological activities of SDE prepared essential oils from flowers and fruits of twoHypericumspecies from central Iran

Abstract: Essential oil (EO) compositions of flowers and fruits of Hypericum perforatum L. and Hypericum scabrum L. growing wild in Kashan, central Iran, were determined by simultaneous steam distillation-solvent extraction method and analysed using GC-MS technique. Analysis revealed 28 identified compounds for H. perforatum, with two main components being α-pinene (25.36%) and α-amorphene (12.12%). Thirty-five compounds were identified in H. scabrum L. representing 98.60% of the oil with α-pinene (70.21%) and p-mentha-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…Different results were reported by Hosni et al (2011). Similarly, the content of a-pinene greatly differs between the EO extracted from flowers (70.2%) and fruits (25.4%) of both H. perforatum and H.scabrum growing wild in Iran (Akhbari et al 2012). Aerial parts of H. perforatum collected during the flowering phenophase contain germacrene D (22.1%), b-caryophyllene (11.3%), a-pinene (8.6%) and a-cadinol (4.4%) as the major constituents in the EO (Chauhan et al 2011).…”
Section: Chemical Composition Of Hypericum Essential Oilsmentioning
confidence: 84%
“…Different results were reported by Hosni et al (2011). Similarly, the content of a-pinene greatly differs between the EO extracted from flowers (70.2%) and fruits (25.4%) of both H. perforatum and H.scabrum growing wild in Iran (Akhbari et al 2012). Aerial parts of H. perforatum collected during the flowering phenophase contain germacrene D (22.1%), b-caryophyllene (11.3%), a-pinene (8.6%) and a-cadinol (4.4%) as the major constituents in the EO (Chauhan et al 2011).…”
Section: Chemical Composition Of Hypericum Essential Oilsmentioning
confidence: 84%
“…According to the extensive phytochemical studies on H. perforatum, it has been reported that the essential oil constituents belong to different chemical classes with a considerable qualitative and quantitative variation in composition (Akhbari et al, 2012;Chauhan et al, 2011;Helmja et al, 2011;Pavlovic et al, 2006;Baser et al, 2002;Erken et al, 2001;Cakir et al, 1997). This variability could be related to the effect of variables such as genetic factors, developmental stages, types of plant materials, methods of extraction, environmental conditions, etc.…”
Section: Introductionmentioning
confidence: 94%
“…However, some studies have to be performed on its volatile compounds in depth because of their potential appli- cations in cosmetology and pharmacology (Schwob et al, 2002). So far, biological activities of essential oils isolated from H. perforatum have been considered in some studies and their antioxidant, larvicidal, antibacterial and antifungal effects revealed (Rouis et al, 2013;Akhbari et al, 2012;Saroglou et al, 2007;Rancic et al, 2005).…”
Section: Introductionmentioning
confidence: 95%
“…Similarly, a-pinene is the major constituents in other Hypericum species (Baser et al, 2002;Couladis et al, 2001;Crockett et al, 2007;Javidnia et al, 2008;Nogueira et al, 2008;Yuce & Bagci, 2012). Akhbari et al (2012) reported that the content of a-pinene differs greatly between the essential oil extracted from flowers (70.2%) and fruit (25.4%) of both H. perforatum and H. scabrum growing wild in Iran. An examination of H. androsaemum by Giuliani et al (2010) indicated that the marginal glands of leaves contained b-caryophyllene and germacrene-B as the dominant volatile constituents, while the laminar glands contained mainly b-pinene and limonene.…”
Section: Chemical Compositionsmentioning
confidence: 99%